Spiritual Intelligence, Emotional Intelligence and Auditor’s Performance - Rustam Hanafi (Jurnal Akuntansi dan Auditing Indonesia, 2010)
The objective of this research was to investigate empirical evidence about influence audi-tor spiritual intelligence on the performance with emotional intelligence as a mediator variable. Linear regression models are developed to examine the hypothesis and path analysis. The de-pendent variable of each model is auditor performance, whereas the independent variable of model 1 is spiritual intelligence, of model 2 are emotional intelligence and spiritual intelligence. The parameters were estimated by questioner data, with of 83 auditor respondent had worked in public accountant firms all of Jawa Tengah and Daerah Istimewa Yogyakarta.Results of testing showed that empirical evidence supports all the proposed hypothesis. With path analysis, this research shows relation of third variables (spiritual intelligence, emo-tional intelligence, and performance) that spiritual intelligence has indirect positive influenced to performance with emotional intelligence as the mediator variable.Keywords: Spiritual Intelligence, Emotional Intelligence, Performance.